Antioxidant and neuroprotective actions of resveratrol in cerebrovascular diseases - Wang, Qing; Yu, Qi; Wu, Min (Frontiers in Pharmacology, 2022)
Cerebral vascular diseases are the most common high-mortality diseases worldwide. Despite its global prevalence, effective treatments and therapies need to be explored. Given that oxidative stress is an important risk factor involved with cerebral vascular diseases, natural antioxidants and its derivatives can be served as a promising therapeutic strategy. Resveratrol (3, 5, 4’-trihydroxystilbene) is a natural polyphenolic antioxidant found in grape skins, red wine, and berries. As a phytoalexin to protect against oxidative stress, resveratrol has therapeutic value in cerebrovascular diseases mainly by inhibiting excessive reactive oxygen species production, elevating antioxidant enzyme activity, and other antioxidant molecular mechanisms. This review aims to collect novel kinds of literature regarding the protective activities of resveratrol on cerebrovascular diseases, addressing the potential mechanisms underlying the antioxidative activities and mitochondrial protection of resveratrol. We also provide new insights into the chemistry, sources, and bioavailability of resveratrol.